SUN-452 Predictive Factors of Recurrence in Cushing's Disease after Successful Transsphenoidal Surgery - Gomes, Vânia (J Endocr Soc, 2019)
Introduction: Successful long-term management in Cushing’s disease (CD) is challenging. Transsphenoidal surgery (TS) is the treatment of choice. Recurrence rates vary from 15–66% within 5-10 years of initially successful surgery. Objective: To evaluate the predictive factors for recurrence in patients with CD submitted to TS. Methods: Retrospective study of 44 patients with CD submitted to TS between 2005 and 2016 in a single tertiary center. Patients were divided into two groups, based on the outcome after TS (remission vs recurrence/persistence of disease), for comparison. Immediate postoperative remission (IPR) was defined as cortisol < 2ug/dL and ACTH <5 pg/mL within 7 days of tumor resection. Recurrence is defined by CD relapse after an initial remission after TS. Different variables were analyzed: age at diagnosis, gender, preoperative basal and dynamic hormonal tests and pituitary MRI, immediate postoperative hormonal tests, histological findings, postoperative hypopituitarism, time to recurrence, and time to recovery of hypothalamo-pituitary-adrenal (HPA) axis. Statistical analysis was performed with SPSS software, version 20. Statistical significance: p < 0.05. Results: From a total of 44 patients, 42 were eligible for the analysis and 2 were excluded due to unknown outcome after TS. The mean age was 40.6 ± 15 years and 90.5% were female. Based on immediate postoperative biochemical evaluation, performed in 35 individuals, only 18 (51,4%) would be considered in remission. Later clinical and biochemical evolution enabled considering 39 patients (92.9%) in remission. At a median follow-up of 6 years (1-21), 23 patients (59%) were still in remission whereas the remaining 41% relapsed; median time to recurrence – 3 years (0.25-17). Recurrence was significantly more frequent in: patients who needed glucocorticoid replacement therapy during less than 6 months after TS (19% vs 77.8%, p=0.004) and patients without histological evidence of adenoma/hyperplasia (75% vs 31%, p=0.04). There were no statistically significant differences between groups concerning the remaining variables studied. Conclusions: Absence of IPR criteria does not allow for conclusion of disease persistence. On the other hand, IPR is not a guarantee of life long remission. In this study, 41% of the patients who achieved surgical remission after TS recurred during long term follow-up making surveillance essential. Rapid recovery of HPA axis and negative histology were predictive factors of recurrence.